Time series analysis and ARIMA models for milk yield data: TIME SERIES ANALYSIS OF MILK YIELD DATA - Kumar, Vinod; Navneet, Navneet Kaur (Indian Journal of Dairy Science, 2024)
Milk production is an important way for farmers to increase their income and provide more nutritious food for their families. Milk production is an important source of income for small and marginal farmers and farm workers. Milk production has become an important source of livelihood in large urban areas where the demand for milk is high. The demand for milk is increasing rapidly in India, especially due to population growth. People are more interested in healthy packaged foods that can be satisfied with dairy products. The country's population is expected to reach 1.5 billion by 2035. In this context, it is important to be aware of developments in recent years and to anticipate future milk supply and demand in order to improve and sustain the growth and development of the sector. Therefore, secondary data was collected from IDF Nagla, Pantnagar, under the College of Veterinary and Animal Science, G.B. Pant University of Agriculture and Technology. Time series analysis was carried out to adjust the data and forecast the milk production for the coming years. Therefore, ARIMA (0,1,1) (1,1,1)12  for Crossbred cows,  ARIMA (1,1,0) (0,1,1)12  for Sahiwal cows and ARIMA (0,1,1) (2,1,0)12 for buffaloes were found to be more appropriate for predicting milk production using GRETL package.